Metabolic risk factors among government employees in Putrajaya, Malaysia - Chee, Huei Phing; Abu Saad, Hazizi; Mohd Yusof, Barakatun Nisak; Mohd Taib, Mohd Nasir (Penerbit Universiti Kebangsaan Malaysia, 2014)
This study aimed to assess the metabolic risk factors among government employees in Putrajaya, Malaysia. Government employees (n=675) were recruited from five government agencies in Putrajaya using a multi-stage random sampling method. Data on socio demographic characteristics, stages of change for physical activity, anthropometric and biochemical and clinical examinations were collected. A total of 154 (23.4%) men and 505 (76.6%) women with the mean age of 34.49±8.80 years participated in this study. The number of government employees that met the metabolic syndrome criteria based on a 'Harmonized' definition (48.9%) was higher than that in the general Malaysian population. High blood pressure was higher in men (56.5%) compared to women (39.8%). The male participants had a significantly higher mean ± standard deviation in all the metabolic risk factors except HDL-cholesterol, compared to a significance level of 0.05 in the female participants. A high proportion of government employees (84.5%) had at least one metabolic risk factor. Men were 54% more likely to have metabolic syndrome than women based on 'Harmonized' definition. Participants in the pre- contemplation stage for physical activity were approximately 17 times more likely to have metabolic syndrome compared to participants in the maintenance stage according to 'Harmonized' definition. In general, this study suggested that a high proportion of government employees (84.5%) had at least one metabolic risk factor. There is a pressing need to commence intervention programs in the workplace to identify and manage government employees at high risk for cardiovascular disease and diabetes.